Editorial - Revitalizing the Graduate Program of the UP SLIS - Buenrostro, Iyra S.
Due to the pandemic, the UP SLIS has faced many challenges in providing educational, administrative and emotional support to our students, faculty and staff, as well as extension services and assistance to our colleagues in the profession. Nevertheless, the UP SLIS continues to thrive and devise ways and ideas to uphold honor and excellence, and fulfill its vital role in educating and training more librarians and information professionals. With the new and revised graduate programs to be offered starting academic year 2022-2023 (i.e., MLIS, MSLIS, MARM), the UP SLIS maintains its mission to deliver outstanding graduate LIS education in the country and in the Southeast Asian region.
Keywords: UP School of Library and Information Studies